Worm-control practices and prevalence of anthelmintic resistance using in vivo FECRTs on smallholder sheep farms in Lithuania - Kupčinskas T.; Stadalienė I.; Šalomskas A.; Trusevičius P.; Varady M.; Petkevičius S. (Helminthologia, 2016)
This study determined the prevalence of anthelmintic resistance (AR) in parasitic nematodes on smallholder sheep farms in Lithuania from April to November 2014. Faecal samples were collected from two groups of 10-15 sheep treated with fenbendazole (FBZ) or ivermectin (IVM) on 18 sheep farms. Two samples were collected from each group: on day zero (T1) and 10-14 days after treatment. Faecal egg counts (eggs per gramme, EPG) were determined using a modified McMaster technique. Animals with < 140 EPG on day zero were removed from the analysis. The prevalence of AR was estimated using the in vivo faecal egg count reduction test. AR to FBZ was detected on three of 15 farms where FBZ was used (20 %) and was suspected on one farm (6.7 %). AR to IVM was detected on two of 16 farms where IVM was used (12.5 %). The main species of resistant gastrointestinal nematodes (GINs) identified after treatment were Teladorsagia spp. and Trichostrongylus spp. A questionnaire surveying 71 sheep farmers estimated that 71.8 % of sheep farmers used anthelmintics against GINs. IVM was the most frequently (68.6 %) applied anthelmintic, and 62.7 % of the respondents reported treating their animals twice a year. This study confirmed the presence of AR to GIN infections on sheep farms in Lithuania. Future studies should assess the prevalence of AR to GIN infection using in vitro methods.